If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2y + 3z)(2y + 3z)(2y + 3z) = 0 Multiply (2y + 3z) * (2y + 3z) (2y * (2y + 3z) + 3z * (2y + 3z))(2y + 3z) = 0 ((2y * 2y + 3z * 2y) + 3z * (2y + 3z))(2y + 3z) = 0 Reorder the terms: ((6yz + 4y2) + 3z * (2y + 3z))(2y + 3z) = 0 ((6yz + 4y2) + 3z * (2y + 3z))(2y + 3z) = 0 (6yz + 4y2 + (2y * 3z + 3z * 3z))(2y + 3z) = 0 (6yz + 4y2 + (6yz + 9z2))(2y + 3z) = 0 Reorder the terms: (6yz + 6yz + 4y2 + 9z2)(2y + 3z) = 0 Combine like terms: 6yz + 6yz = 12yz (12yz + 4y2 + 9z2)(2y + 3z) = 0 Multiply (12yz + 4y2 + 9z2) * (2y + 3z) (12yz * (2y + 3z) + 4y2 * (2y + 3z) + 9z2 * (2y + 3z)) = 0 ((2y * 12yz + 3z * 12yz) + 4y2 * (2y + 3z) + 9z2 * (2y + 3z)) = 0 Reorder the terms: ((36yz2 + 24y2z) + 4y2 * (2y + 3z) + 9z2 * (2y + 3z)) = 0 ((36yz2 + 24y2z) + 4y2 * (2y + 3z) + 9z2 * (2y + 3z)) = 0 (36yz2 + 24y2z + (2y * 4y2 + 3z * 4y2) + 9z2 * (2y + 3z)) = 0 Reorder the terms: (36yz2 + 24y2z + (12y2z + 8y3) + 9z2 * (2y + 3z)) = 0 (36yz2 + 24y2z + (12y2z + 8y3) + 9z2 * (2y + 3z)) = 0 (36yz2 + 24y2z + 12y2z + 8y3 + (2y * 9z2 + 3z * 9z2)) = 0 (36yz2 + 24y2z + 12y2z + 8y3 + (18yz2 + 27z3)) = 0 Reorder the terms: (36yz2 + 18yz2 + 24y2z + 12y2z + 8y3 + 27z3) = 0 Combine like terms: 36yz2 + 18yz2 = 54yz2 (54yz2 + 24y2z + 12y2z + 8y3 + 27z3) = 0 Combine like terms: 24y2z + 12y2z = 36y2z (54yz2 + 36y2z + 8y3 + 27z3) = 0 Solving 54yz2 + 36y2z + 8y3 + 27z3 = 0 Solving for variable 'y'. The solution to this equation could not be determined.
| 3x-7=39 | | 5+x=8-2x | | 7-5a=-a(3a+5) | | -2=5x-28 | | Y=7.5(20) | | csinx=0 | | cx+d=e | | x^7-2x^6-8x^5=0 | | 7-5a=a-(3a+5) | | -2x^4+10x^2-8=0 | | 6x^2+37x+155=0 | | 120x+50(230-50)=17100 | | (x-4)(x-5)(x-8)(x-10)=72x2 | | 8+3x=20-3x | | x-2[x-3(x-4)]=4x-3[x-2(x-1)] | | 12+10z-12z=12-2z | | 5x+6=x-6 | | w/2+w/3+w/4=13 | | 5k-10=-20 | | 10b+4-b-8= | | t+6/4=5t/8 | | -x^4+2x^2-2=0 | | -5*81-6*-9-7= | | 6d+3(1+d)=(d-7)-2d | | z^4+z^3+z^2-4z+10=0 | | 5*14+8= | | 9x^2=25-9 | | x-7=82y+3x | | 2/x^3=54 | | 70h=40 | | y^4-y^3+8y^2-8y^1+4y=0 | | y^5-y^4+8y^3-8y^2+4y=0 |